العمارة السكنية المعاصرة في الساحل السوري / نحو عمارة محلية واعية / (مدينة اللاذقية أنموذجاً) - ديوب, طالب; حسين, هلا (Latakia University Journal -Engineering Sciences Series, 2019)
إن العمارة المعاصرة وما ينتج عنها من نظريات حديثة و مفاهيم جديدة خلقت شكلا" من أشكال النزاع مع كل ما هو قديم و موروث إضافة إلى ضعف الارتباط الحقيقي بالبيئة الطبيعية. اختير الساحل السوري بوصفه مكاناً جغرافياً للدراسة في زمان نحنّ فيه إلى التاريخ، وكانت مدينة اللاذقية هي المثال الذي ستجرا عليه الدراسات ضمن نطاق البحث الجاد والفكر المنفتح على كل ما هو جديد في عالم العمارة و تطويعه لخلق عمارةٍ مفعمةٍ بروح التراث ومستجيبةٍ لنداء الطبيعة، و هذا ما نقصد به العمارة الواعية التي هي شكل جديد يبدو أكثر ذكاء في التعامل مع معطيات العصر الحديث من خلال وعيها في التعامل مع الإنسان الذي صنعت العمارة لأجله، مع الإرث الفكري والثقافي والمعماري ، ومع الطبيعة المحيطة بالإنسان. Contemporary architecture, and its emerging modern theories and concepts, has brought about some sorts of conflict with everything old and inherited, and weakened the link with natural environment The Syrian coast has been selected as a geographical location at a time during which we experience historical nostalgia. The city of Latakia was, moreover, the considered case, within the framework of sensible research and thought open to everything new in the world of architecture, which can be adapted to devise an architectural style, colored with classical taste, and responsive to the appeal of nature. In our view, this is the indication of Gentle Architecture, which is a new architectural style, seemingly more intelligent in dealing with the requirements of the modern age, through its sensibility in dealing with altogether the human being for whom architecture was invented, the intellectual, cultural and architectural heritage and the human being's surrounding environment.